Diversifier les figures du public : l’appropriation du patrimoine culturel sur le Web - Nathalie Casemajor Loustau (Communication)
Cultural institutions see the Web as a tool for broadening their audience base, thanks to the digitization of heritage collections, but what sort of “new audiences” can be reached through the Web? Setting aside the quantitative aspect of audience broadening, the author proposes instead to think about the diversification of public representations, that is to say the anticipation of audience roles and practices as they are embedded in the socio-technical design of the website, shaping the interaction with contents online.